Healthcare professionals' views on discussing fertility preservation with young cancer patients: a mixed method systematic review of the literature - Vindrola‐Padros, Cecilia; Dyer, Karen E.; Cyrus, John; Lubker, Irene Machowa (Psycho-oncology (Chichester, England), 2017)
Objective In spite of efforts to guarantee patients are adequately informed about their risk of fertility loss and offered treatment for fertility preservation (FP), previous studies have reported that this topic is not routinely discussed with patients, especially with younger patient populations. A mixed method systematic review was undertaken to explore the factors shaping the discussion of FP with children (0–15 years) and adolescents/young adults (16–24 years) with cancer. Methods Six databases were searched independently using a combination of keywords and controlled vocabulary/subject headings relating to cancer and fertility. Inclusion criteria consisted of: (a) being published in a peer‐reviewed journal, (b) a focus on healthcare professionals' (HCPs') beliefs, attitudes, or practices regarding fertility issues in cancer patients, (c) primary data collection from HCPs, and (d) a focus on HCPs who provide services to young patients. Of the 6276 articles identified in the search, 16 articles presenting the results of 14 studies were included in the final review. Results Common themes reported across studies indicate that five main factors influence HCPs' discussion of FP with young cancer patients: (a) HCPs' knowledge, (b) HCPs' sense of comfort, (c) patient factors (i.e., sexual maturity, prognosis, partnership status, and whether or not they initiate the conversation), (d) parent factors (i.e., HCPs' perception of the extent of their involvement), and (e) availability of educational materials. Conclusions Future work should ensure that HCPs possess knowledge of cancer‐related FP and that they receive adequate training on how to consent and discuss information with young patients and their parents.